On Laburn’s ‘mystery’ query – A prehistory of the Vaal River as water source of the Witwatersrand (1887-99) (Historia, 2021)
The discovery of gold and subsequent development of Johannesburg and the Witwatersrand as from 1886 gave rise to a signficant growth in the demand for water. In a 1979 publication, R. Laburn explained that it was a 'mystery' why the Vaal River was not already put to use in the nineteenth century to provide water to one of the largest industrial conurbations in Southern Africa. In the study an attempt is made at providing some answers. It appears as if practical and political considerations prevented the Vaal River - which in the twentieth century became the major supplier of water to the Witwatersrand - from being used. It was an expensive venture. There were however also a number of political factors which undermined the plans which had been made from as early as 1889.
Keywords: Laburn, R.J., Vaal River Concession; Drought conditions; Free marketeers; Water provision; Consumption patterns; Vaal River Scheme; Zuurbekom; Local government developments; Witwatersrand; History